Sosiologi Kesehatan Dalam Praktik: Pelatihan Dan Penyuluhan Perubahan Gaya Hidup Untuk Mengurangi Risiko Asam Urat Pada Komunitas Lansia Desa B Tahun 2025 - Meiana Harfika; Jukarnain Jukarnain; Nurhaedah Nurhaedah; Nursinah Nursinah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Gout or gouty arthritis cases are increasing among the elderly due to unhealthy lifestyles, such as high-purine food consumption, lack of physical activity, and minimal awareness of the importance of healthy behaviors. This community service activity aims to improve the knowledge and behavior of the elderly in preventing gout through a sociology of health approach, which emphasizes behavioral change based on social interactions, cultural values, and community norms. The implementation method included counseling, training in healthy lifestyle practices, group discussions, and pre- and post-test evaluations. The activity was conducted in Village B, South Sulawesi, involving 30 elderly participants. The materials provided included education on low-purine nutrition, light physical exercise, and the formation of a social support group